2015
DOI: 10.1155/2016/7909380
|View full text |Cite
|
Sign up to set email alerts
|

Is Modulation of Oxidative Stress an Answer? The State of the Art of Redox Therapeutic Actions in Neurodegenerative Diseases

Abstract: The central nervous system is particularly sensitive to oxidative stress due to many reasons, including its high oxygen consumption even under basal conditions, high production of reactive oxygen and nitrogen species from specific neurochemical reactions, and the increased deposition of metal ions in the brain with aging. For this reason, along with inflammation, oxidative stress seems to be one of the main inducers of neurodegeneration, causing excitotoxicity, neuronal loss, and axonal damage, ultimately bein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
87
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 122 publications
(88 citation statements)
references
References 106 publications
1
87
0
Order By: Relevance
“…The brain is particularly vulnerable to oxidative stress due to its high oxygen consumption and high production of reactive oxygen and nitrogen species. Accumulating evidence has demonstrated that oxidative stress plays an important role in excitotoxicity, axonal damage and neuronal death (Chiurchiu et al, 2015), and is involved in the onset and progression of several neurodegenerative diseases, such as AD, PD, HD, and amyotrophic lateral sclerosis (ALS) (Radi et al, 2014; Cobb and Cole, 2015). Oxidative stress also plays an important role in TD-induced brain damage (Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The brain is particularly vulnerable to oxidative stress due to its high oxygen consumption and high production of reactive oxygen and nitrogen species. Accumulating evidence has demonstrated that oxidative stress plays an important role in excitotoxicity, axonal damage and neuronal death (Chiurchiu et al, 2015), and is involved in the onset and progression of several neurodegenerative diseases, such as AD, PD, HD, and amyotrophic lateral sclerosis (ALS) (Radi et al, 2014; Cobb and Cole, 2015). Oxidative stress also plays an important role in TD-induced brain damage (Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The brain is particularly susceptible to oxidative stress for many reasons. First and foremost, although it comprises only 2% of total body weight the brain consumes 20% of the body’s total oxygen supply, with a significant portion of that oxygen subsequently being converted into reactive oxygen species (ROS) (7, 8, 9). Secondly, in the brain there are specific neurochemical reactions, like dopamine oxidation, which create large amounts of reactive oxygen or nitrogen species (ROS, RNS).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Thirdly, the brain has large amounts of lipids (e.g., myelin), which are sensitive to oxidative stress. Lastly, with aging there is increased deposition of metal ions in the brain, which are catalysts in the production of ROS and RNS (9, 10). …”
Section: Oxidative Stressmentioning
confidence: 99%
“…Although the clinical manifestations differ for these disorders, a common denominator in their pathology is the induction of oxidative stress [7, 8]. For the past several decades, evidence has accumulated supporting oxidative stress as an underlying common denominator of brain injury and neurodegenerative disorders.…”
Section: Introductionmentioning
confidence: 99%